2017
DOI: 10.1111/exd.13464
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide association study identifies GALC as susceptibility gene for mucous membrane pemphigoid

Abstract: Mucous membrane pemphigoid (MMP) is a rare, chronic and often aggressive subepidermal autoimmune blistering disease potentially affecting several mucous membranes with blisters and secondary erosions and scars. The pathogenesis of MMP is poorly understood, and the contribution of genetic predispositions, other than HLA class II allele variants to MMP, is unknown. The objective of this study is to identify susceptibility genes for MMP in a British cohort of MMP patients. A GWAS was conducted in a British cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“… 123 , 124 , 125 , 126 A genome‐wide association study found 38 single‐nucleotide polymorphisms associated with MMP; these polymorphisms need functional validation. 126 In a few cases, drug‐induction of MMP has been described. 127 , 128 , 129 Dipeptidyl peptidase‐4 inhibitors may be associated with the induction of MMP.…”
Section: Clinical Presentationmentioning
confidence: 99%
“… 123 , 124 , 125 , 126 A genome‐wide association study found 38 single‐nucleotide polymorphisms associated with MMP; these polymorphisms need functional validation. 126 In a few cases, drug‐induction of MMP has been described. 127 , 128 , 129 Dipeptidyl peptidase‐4 inhibitors may be associated with the induction of MMP.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…A different genetic basis may conceivably explain the different results achieved by these studies. Genetic factors determine the targeted autoantigens or epitopes of MMP, but they may also regulate their different expression between the skin and mucous membranes …”
mentioning
confidence: 99%
“…Previous studies have reported an association of pemphigus and pemphigoid disease susceptibility with certain HLA alleles, the association of bullous pemphigoid with several polymorphisms with the Fc gamma receptor locus, ST18 in pemphigus, and mitochondrial alterations in bullous pemphigoid patients . In this FTI, a genomewide association study with 106 MMP patients and over 8,000 controls identified 38 single nucleotide polymorphisms (SNP) . Of these, in addition to the HLA locus, an association of mucous membrane pemphigoid (MMP) with rs17203398, located intronically in the β‐galactocerebrosidase gene ( GALC ), was replicated and confirmed in an independent cohort.…”
Section: Translational and Clinical Research In Pdmentioning
confidence: 90%